Promising Prodiginins Biological Activities - Ladetto, María Florencia (2025)
Prodigionins is large family of at least 34 pyrrolic compounds including the well-studied red pigment prodigiosin. Prodigionins are produced by several microorganisms displaying broad biological activities including antimicrobial, antiviral, antiparasitic, antiproliferative, and immunosuppressive activities. The present review aims to compile and analyze the main physicochemical and biological properties and mechanisms of action of prodigionins for the treatment of microbial diseases, particularly SARS-CoV-2 disease and the opportunistic infections related to COVID-19. The interaction of prodigiosin, as a model molecule, with cellular membranes, potential drug delivery devices, and toxicological studies, and in silico studies using molecular dynamics showed that the prodigiosin motif, which interacts with lipids, opens a new door for the potential therapeutic use of prodigionins.